Comparison of Post Transurethral Resection of the Prostate Patients Outcome Presenting with or without Acute Retention of Urine - Lingesh Sairam Chelliah; Sathish Kumar G. (Medical Research and Its Applications Vol. 5, 2024)
Introduction: Benign Prostate Hyperplasia (BPH) is most common in elderly people and is the most common cause of lower urinary tract symptoms. It affects roughly 10% of men under the age of 40, while in men over 80, it affects 80% of them. Failure to recognize these symptoms leads to the progression of the disease process that may ultimately lead to Acute urinary retention (AUR). An analysis of post-TURP (Transurethral Resection of the Prostate) complications between patients presenting with and without AUR was done. And found that early intervention helped in preventing better recovery of patients with minimal acceptable complications than in those who had acute urinary retention and this study provides educational insight to patients about the need for early intervention in patients presenting with LUTS (Lower Urinary Tract Symptoms). Aim: To compare the post-TURP outcome and complications of Benign Prostatic Hyperplasia patients presenting with and without Acute Urinary Retention. Materials and Methods: This is a prospective study. Patients with LUTS secondary to Benign Prostatic Hyperplasia and who presented with and without Acute Urinary Retention were included in the study. Patients were analyzed with detailed History and Physical examination, Digital Rectal Examination, S.PSA, USG KUB, Bladder Wall Thickness Uroflow and Post Void Residual urine. Patients who were more than 75 years old, men with neurological disease, prostate cancer, urethral stricture, and previous prostate or urethral surgery were excluded. Patient proforma containing patient particulars, operative details and one-month follow-up were performed here. Post-operative variables that were evaluated are Post op UTI, sepsis, Re-catheterisation rate, resurgery, onset of TUR syndrome, persistent hematuria requiring blood transfusion, post-op stricture, LUTS, Q max, PVR and length of hospital stay, compared between the two groups. Results: The study finding includes significant distribution in age distribution in patients presenting with and without acute urinary retention. Patients experiencing acute urinary retention are typically of advanced age and present late, resulting in a higher prostate volume and an associated increase in S.PSA levels and when these patients when undertaken for surgery tend to have increased post-operative incidence of UTI and need for recatheterisation rate thereby causing prolonged hospital stay. The incidence of TUR syndrome Hematuria and the need for blood transfusion were comparable between the two groups. Conclusion: The study clearly shows that patients with advanced age have an increased risk of presenting with Acute Urinary Retention. Thus this study acts as educational insight to patients stressing the need for early intervention in BPH as incidence of age and associated complications like post-operative UTI and an increased need for Recatheterisation and prolonged hospital stay.